Knowledge and Use of Wild Edible Plants in the Hula District of the Sidama Zone - Sina, Benta; Degu, Hewan Demissie (International Journal of Bio-resource and Stress Management, 2015)
Sidama Zone is found in the Southern Nation Nationalities and People Regional State of Ethiopia. The zone has thirty-three districts. Wild edible plants are means of survival during war, political unrest, and food insecurity in this Zone. The objective of this research is to describe indigenous knowledge about wild edible plants based age, gender and education level in Hula district. Data on the use of wild edible plant were collected through semi structured interviews with key informants. The textual data were coded, quantified and analyzed with R software. A total of 50 wild edible plants belonging to 46 genera and 31 botanical families were reported in Hula district. Families Moraceae (12.5%), Rosaceae (12.5%), Rubiaceae (9.5%), Fabaceae (9.5%) and Solanaceae (9.5%) were found in the area. About 68% of the wild edible plants were trees. These wild edible plants were marketable. Further more some of the wild edible plants have medicinal values for human and livestock diseases. The popular food-category of wild edible plants is fruit eaten raw, and herbs eaten cooked as vegetables. There is significant difference (p<0.05) on the knowledge of wild edible plants between different sex and age groups. Social, economic and cultural factors contributed for consumption and avoidance of some edible wild plants. The poor communication system, on the other hand, has hindered the knowledge transfer from elders to youngsters and among different genders. The demand is growing for most of the wild plants regarded as local specialties, and reflect regional and cultural identity.